Real-Time SPR Biosensing to Detect and Characterize Fast Dissociation Rate Binding Interactions Missed by Endpoint Detection and Implications for Off-Target Toxicity Screening - William Martelly; Rebecca L. Cook; Chidozie Victor Agu; Lydia R. Gushgari; Salvador Moreno; Sailaja Kesiraju; Mukilan Mohan; Bharath Takulapalli (Biomolecules)
Accurate detection of biomolecular interactions is essential in many areas, from the detection of the presence of biomarkers in the clinic to the development of therapeutic drugs and biologics in biopharma to the understanding of various biological processes in basic research. Traditional endpoint approaches can suffer from false-negative results for biomolecular interactions with fast kinetics. By contrast, real-time detection techniques like surface plasmon resonance (SPR) monitor interactions as they form and disassemble, reducing the risk of false-negative results. By leveraging cell-free expressed proteins captured on either glass or SPR biosensors and using two different commercial antibodies with variable off-rates that both target HaloTag antigens as a model, we compare and contrast results from a fluorescence endpoint assay versus real-time sensor-integrated proteome on chip (SPOC®) SPR-based detection. In this study, we illustrate the limitations of the representative immunofluorescent endpoint assay when investigating transient interactions characterized by fast dissociation rates. We highlight the importance of choosing reagents well suited to the selected assay, as well as the importance of considering binding kinetics and protein ligand conformational states when interpreting results from binding assays, especially for applications as critical as the off-target screening of therapeutics.